The Influence of Work Motivation and Organizational Commitment on Employee Performance with Job Satisfaction as a Mediating Variable at the Indonesian Health Service Association (Adinkes) - Shimponie Tania Wijaya Sipayung; Tine Yuliantini (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effects of work motivation and organizational commitment on employee performance, with job satisfaction as a mediating variable, within ADINKES in Indonesia. The population comprised 100 employees, and a sample of 80 respondents was determined using Slovin’s formula (e=0.05) through simple random sampling. Primary data were collected via five-point Likert scale questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SmartPLS 4). The findings show that work motivation and organizational commitment have positive and significant effects on job satisfaction, while job satisfaction positively and significantly influences employee performance. In addition, motivation and commitment also exert direct effects on performance, with organizational commitment being the most dominant predictor. The R² for employee performance is 0.849, indicating that 84.9% of performance variance is explained by the model, while the R² for job satisfaction is 0.462. Predictive relevance (Q²) indicates good model quality, with the strongest contribution on the commitment→performance path. These results underscore the importance of HR strategies—meaningful job design, fair reward systems, workload management, and supportive leadership—to sustainably enhance job satisfaction and employee performance at ADINKES..